Prevalence of Lymphoma Cancer in Punjab, Pakistan - Nawaz, Muhammad Zohaib; Bilal, Muhammad; Mehmood, Muhammad Aamer; Asgher, Muhammad (International Journal of Applied Sciences and Biotechnology, 2015)
Pakistan has a high magnitude of cancer from its independence. The burden of lymphoma cancer continues to increase in Pakistan. The low socioeconomic districts of Punjab such as those in Faisalabad most severely affected by lymphoma. The objective of this study was to analyze the lymphoma cancer registry record of patients from the districts in Faisalabad in order to achieve a net lymphoma incidence for use in raising future health program against cancer. The medical records of 110 patients registered at the Punjab Institute of Nuclear Medicine in Faisalabad were investigated. Information regarding age, gender, socioeconomic status, affected sites and cancer type were obtained. Among 110 cases of lymphoma cancer, the male: female ratio was 3:1, with an age range of 5-85 years. Of the 110 patients, 74% were male and 26% were female. Similar to the subtype distribution of lymphoma in the different areas of Faisalabad and its surroundings, Non-Hodgkin’s lymphoma (NHL) was more frequent, 74 cases (67%) than Hodgkin’s disease (HD), 36 cases (33%).The leading cancers were breast 36% (n=248), lymphoma 16% (n=110), and prostate cancer 10% (n=68). The growing burden of cancer especially lymphoma in Faisalabad is extremely alarming. Since the current work was an initial investigation, it could play a leading role in prevention and future planning regarding the battle against lymphoma in Pakistan. Int J Appl Sci Biotechnol, Vol 3(2): 342-346 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12756